(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This paper utilizes a historical-philological approach toexamine one by one a letter written by Abilpeiz to the military governor of Yili in 1775 for his father-in-law Bozuk and the Oyirad woman who fled with her children, and its Manchu translation, including its Latin transcription and modern Kazakh translation. Furthermore, these documents elucidate the literary significance and linguistic characteristics of Kazakh history, language and culture and Kazakh-Oyirad relations. It was the first attempt to study letters in diachronous terms, to study the history of the Kazakh literary language of the eighteenth century using archival materials with translations into Manchurian and Kazakh languages. In the article of the letter, the Abilpeiz of the Sultan is considered as a folk culture as a whole and is studied in conjunction with the customs, rites and beliefs of both the distant ancestors of the Kazakhs and the Kazakh ethnos proper. It was this approach that determined the structure and purpose of the article, which allowed us to show the genesis and evolution of the genres of epistolary writing from the earliest, syncretic forms to full-fledged art formations, to reveal the ancient foundations of classical plots and motifs.